Uneven Development: East Kalimantan 1850-1950 A Preliminary Survey - Soegijanto Padmo (Humaniora, 1997)
The dynamic of economic change occurring in East Kalimantan during 1850 - 1950 period was more or less affected by the interaction between the existing traditional and modern economy. In other words, a group ofpeople of particular area or particular job enjoyed better lifelihood through utilizing economic opportunity created by trading activities and modern industry while others did not. We begin with the trading activities and then followed by agriculture versus timber and mining industry at the end.